SIMULATION OF AIR FLOW PATTERNS INSIDE AN EXPERIMENTAL STACK - Shahzad, F.; Ahmad, M. I.; Sardar, S.; Irfan, N. (The Nucleus, 2012)
To conduct dispersion studies, an experimental facility as a 100 feet high stack is intended to be installed in the premises of a research institute i.e. Pakistan Institute of Engineering and Applied Sciences (PIEAS) in Islamabad. The purpose of this stack is to release an inert gas as a tracer and to collect its ground level concentration data around the source. This data would be helpful in order to validate the modeling results from air dispersion studies. In view of above, present study has two main objectives. First is to evaluate the discharge flow rate of a blower at the manhole of experimental stack which must be capable to produce a maximum velocity of 8m/sec for a tracer emission at the top of the stack. The second aim is to investigate the probability of reversal flow of the tracer entering into stack from an opening located at a proposed height of stack while adjusting the blower flow rate to acquire the desired exit velocity of tracer. To get aforesaid goals, a computer program named FLUENT 6.3 as a Computational Fluid Dynamics (CFD) modeling tool has been employed for the simulation of air flow patterns inside the experimental stack. The results reveal that the blower flow rate of 7650 cfm through manhole of the stack is needed to acquire the exit velocity of 8 m/sec at the top of the stack and there is no possibility of reversal flow of tracer entering from the inlet opening of the stack.